"M.C. Rajah: Pioneering the Modern Subaltern Movements in Madras and Beyond" - Venkatesh.R (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Abstract Rao Bahadur MC. Mailai Chinnathambi Pillai Raja (17th June 1883 – 20th August 1943), popularly known as Raja, was a Scheduled Caste politician and social activist from Tamil Nadu. Even before Ambedkar, he worked for the welfare and progress of Scheduled Caste (SC) people all over India. In the list of activists who have worked for the welfare of the grassroots and to establish equality, M.C. Rajah has the most significant role of in India. It is a matter for everyone to ponder whether is fulfilled. This study is to describe information about M.C Rajah who gave ideas like Ambedkar's contribution to social progress.